Contra nuestro feudalismo: Intelectuales y política en la expansión del georgismo en Argentina (Córdoba, 1914-1924) - Ezequiel Grisendi (Nuevo mundo - Mundos Nuevos, 2015)
Since the late nineteenth century, the intellectual production of the american Henry George concentrated interest in Brazil, Uruguay and Argentina. The Georgist ideas were recovered by politicians, academics, middle-class professional sectors, traders and workers in order to build a refreshing solution to the problem of urban and rural poverty. The "social question" was the result, for Georgists, of the maintenance of a system of land ownership and a tax system more favorable to powerful landowners groups. From 1910, in Argentina Georgism scored a prominently place in public debates about the legitimacy of the tax, the permanence of large estates and labor unrest. Political and intellectual figures in Georgism found a new way of approaching social and economic problems boosted with the beginning of the Great War. While in Buenos Aires had a bounded visibility, georgism showed particularly dynamic urban centers of the Pampas. Cordoba, a city in the center of the country, combined the Georgist proposal with local liberal tradition from its articulation with the political experience of “red radicalism", the secular cultural associations and university intellectual reformists of 1918.